Efektifitas Daya Hambat Larutan Ekstrak Siwak Terhadap Pertumbuhan Bakteri Pada Plak Gigi - Ratih Larasati (Jurnal Skala Husada : The Journal of Health, 2022)
ABSTRACTThe problem in the study is the accumulation of dental plaque and tongue causing decreased dental hygiene. This allows the normal flora in the mouth to become a pathogen that causes tooth decay, thus increasing the DMF-T index. The purpose of this research is to know the effectiveness of inhibitory solution of siwak extract in killing the bacteria in dental plaque. This research was purely experimental in the form of Post-test control group design. This research was conducted in the laboratory, and clinic of Dentistry Department of Poltekkes Kemenkes Surabaya. Selected respondents should fit inclusion criteria. The results of this study were not formed inhibition zone on the plate for bacterial seedling in the negative control group, whereas in the positive control group the mean diameter of the inhibit zone was 27,5 mm. Siwak extract solution concentration 50% more effective than 25% siwak extract solution. Siwak extract solution effectively inhibited bacterial growth from dental plaque (p 0.05). However, chlorhexidine 0.2% is more effective in inhibiting bacterial growth from dental plaque than siwak extract solution.ABSTRAKMasalah dalam penelitian ini adalah akumulasi plak pada gigi dan lidah yang menyebabkan buruknya kebersihan gigi. Flora normal dalam keadaan tertentu di dalam mulut dapat berubah menjadi patogen yang menyebabkan gigi karies, sehingga meningkatkan indeks DMF-T. Tujuan penelitian ini adalah mengetahui efektifitas daya hambat larutan ekstrak siwak dalam membunuh bakteri pada plak gigi. Metode penelitian ini adalah eksperimen murni dengan desain Post-test control  group. Penelitian dilakukan di laboratorium, dan klinik Jurusan Keperawatan Gigi Poltekkes Kemenkes Surabaya. Responden yang dipilih harus sesuai kriteria inklusi. Hasil penelitian, tidak terbentuk zona hambat pada lempeng bakteri kelompok kontrol negatif, sedangkan pada kelompok kontrol positif diameter rata-rata zona hambat adalah 27,5 mm. Larutan ekstrak siwak konsentrasi 50% lebih efektif daripada larutan ekstrak siwak 25%. Larutan ekstrak siwak efektif menghambat pertumbuhan bakteri dari plak gigi (p 0,05). Walaupun demikian, klorheksidin 0,2% lebih efektif menghambat pertumbuhan bakteri dari plak gigi daripada larutan ekstrak siwak.